Analysis of Membrane Type-1 Matrix Metalloproteinase (MT1-MMP, MMP14) in Eutopic and Ectopic Endometrium and in Serum and Endocervical Mucus of Endometriosis - Maoga, Jane B.; Riaz, Muhammad A.; Mwaura, Agnes N.; Mecha, Ezekiel; Omwandho, Charles O. A.; Scheiner-Bobis, Georgios; Meinhold-Heerlein, Ivo; Konrad, Lutz; Justus Liebig University Giessen (My University, 2023)
Background: Membrane type-matrix metalloproteinases (MT-MMPs) are a subgroup of the matrix metalloproteinases (MMPs) family and are key molecules in the degradation of the extracellular matrix. Membrane type-1 matrix metalloproteinase (MT1-MMP, MMP14) is often deregulated in different cancer tissues and body fluids of human cancer patients; however, MT1-MMP levels in endometriosis and adenomyosis patients are currently unknown. Materials and Methods: Tissue samples from patients with and without endometriosis or adenomyosis were analyzed with immunohistochemistry for the localization of MT1-MMP. Serum and endocervical mucus samples from patients with and without endometriosis or adenomyosis were investigated with MT1-MMP ELISAs. Results: MT1-MMP was localized preferentially in the glands of eutopic and ectopic endometrium. MT1-MMP protein levels are significantly reduced in ovarian endometriosis (HSCORE = 31) versus eutopic endometrium (HSCORE = 91) and adenomyosis (HSCORE = 149), but significantly increased in adenomyosis (HSCORE = 149) compared to eutopic endometrium (HSCORE = 91). Similarly, analysis of the levels of MT1-MMP using enzyme-linked immune assays (ELISAs) demonstrated a significant increase in the concentrations of MT1-MMP in the serum of endometriosis patients (1.3 ± 0.8) versus controls (0.7 ± 0.2), but not in the endocervical mucus. Furthermore, MT1-MMP levels in the endocervical mucus of patients with endometriosis were notably reduced in patients using contraception (3.2 ± 0.4) versus those without contraception (3.8 ± 0.2). Conclusions: Taken together, our findings showed an opposite regulation of MT1-MMP in the tissue of ovarian endometriosis and adenomyosis compared to eutopic endometrium without endometriosis but increased serum levels in patients with endometriosis.
Keywords: ddc:610